Comparative analysis of bifacial and monofacial FPV system in the UK - Mohammed Al Araimi; Mohamed Al Mandhari; Aritra Ghosh (Solar Compass)
Floating photovoltaic (FPV) systems offer an effective solution to land-use constraints and efficiency challenges in traditional ground-mounted photovoltaic (PV) systems. This study investigates the performance of bifacial and monofacial TOPCon PV panels with power ratings of 460 W and 420 W, respectively, in an FPV setup under temperate UK conditions. Addressing a gap in experimental data for such climates, the experiment was conducted at the University of Exeter's Penryn campus. Results show that bifacial panels achieved an average efficiency of 19.64 %, outperforming monofacial panels by 6.59 %. At high irradiance of 1043 W/m², bifacial panels generated a maximum power output of 401.7 W, compared to 391 W for monofacial panels. Even under low irradiance conditions (228 W/m²), bifacial panels maintained an advantage, producing 127.4 W versus 85.43 W for monofacial panels. Thermal analysis demonstrated that bifacial panels exhibited superior cooling, with a top-bottom temperature differential of 1.71 °C, compared to 3.51 °C for monofacial panels. The bifacial gain peaked at 19 % under low irradiance, reducing to 5 % at higher irradiance levels. These results highlight the potential of bifacial FPV systems to enhance energy generation and improve thermal stability in regions with diffuse solar radiation. The findings provide valuable insights for optimizing FPV system designs and suggest that bifacial panels are a promising technology for maximizing solar energy production in temperate climates.